Anticorrosive coating and preparation method thereof

By using nano-grade zinc powder particles in anticorrosion coatings and using electrochemical protection principles, the problem of corrosion in steel structures in industrial plants is solved, and effective anticorrosion effect and extension of steel structure life are achieved.

CN119735974APending Publication Date: 2025-04-01SHANGHAI ZHONGCAI ENG DETECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848849.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When the steel structures of large industrial plants are exposed to industrial environments for a long time, they are susceptible to corrosion damage, resulting in reduced structural safety and durability, thereby increasing maintenance costs and safety risks.

Method used

Nano-scale zinc powder particles are used as the anode material. Based on the principle of electrochemical protection, the zinc powder particles are dispersed into the anticorrosion coating, so that the coating has electrochemical anticorrosion properties.

Benefits of technology

By replenishing electrons on the surface of the steel structure, preventing oxidation, forming a strong protective barrier, effectively preventing corrosion, extending the service life of the steel structure, and the preparation method is simple and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190024200000081
    Figure BDA0005190024200000081
Patent Text Reader

Abstract

The present invention provides an anticorrosive coating and a preparation method thereof, which utilizes an electrochemical protection mechanism and uses nano-sized zinc powder as an anode component. Since the chemical activity of metal zinc exceeds that of steel structures, it can react preferentially under harsh corrosion conditions, effectively providing electrons to the surface of the steel structure, so that the electrons on the surface of the steel structure can be replenished, thereby preventing the steel structure of the industrial plant from being damaged by oxidation corrosion and significantly extending its service life. At the same time, the preparation process of the anticorrosive coating is simple and suitable for industrial large-scale production and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings, and particularly relates to an anti-corrosion coating and a preparation method thereof. Background Art

[0002] Large industrial plants are the backbone of modern industrial production, and their construction quality and durability have a decisive impact on the production efficiency and economic benefits of enterprises. Steel structures are widely selected as the building skeleton of large industrial plants due to their high strength, light weight, good seismic performance and other excellent properties. However, with the long-term exposure of steel structures in industrial environments, the corrosion problem has become increasingly serious, which poses a severe challenge to the safety and durability of the structure. Corrosion not only reduces the load-bearing capacity of steel and increases the cost burden of maintenance, but also may cause structural failure and cause safety accidents in the case of severe corrosion. Therefore, adopting effective anti-corrosion strategies is crucial to maintaining the continuous and stable operation of industrial plants. Summary of the invention

[0003] In view of the above technical problems, the purpose of the present invention is to provide an anti-corrosion coating and a preparation method thereof. Based on the principle of electrochemical protection, nano-scale zinc powder is selected as the anode material, and the metallic zinc is prepared into nano-scale particles and then dispersed into the coating, so that the coating has certain electrochemical anti-corrosion properties.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] An anti-corrosion coating comprises zinc powder particles and a solvent matrix. The particle size of the zinc powder particles is nanometer-scale, and the mass percentage of the zinc powder particles in the anti-corrosion coating is 1-15wt.%.

[0006] In some technical schemes, the solvent matrix includes a binder, a modifier, a pH adjuster and a film-forming agent, and the mass percentages of the binder, the modifier, the pH adjuster and the film-forming agent in the anti-corrosion coating are 30-58wt.%, 0.5-1.2wt.%, 1-3wt.% and 20-35wt.%, respectively.

[0007] In some technical solutions, the binder is sodium water glass; the modifier is a water glass modifier; the pH adjuster is ammonium acetate; and the film-forming agent is a water-based hydroxypropyl resin.

[0008] In some technical solutions, the water glass modifier is any one of sodium dodecyl sulfate, sodium carboxymethyl cellulose, and dipotassium hydrogen phosphate.

[0009] In some technical solutions, the zinc powder particles have a particle size of 50nm-90nm.

[0010] The present invention also provides a method for preparing the anti-corrosion coating, wherein the zinc powder particles are dispersed in the solvent matrix to obtain the anti-corrosion coating.

[0011] In some technical schemes, the preparation method also includes: preparing the solvent matrix: weighing the binder, modifier, pH adjuster and film-forming agent according to the ratio, first diluting the binder, then adding the modifier and pH adjuster in sequence and stirring, adding the obtained mixture dropwise to the film-forming agent, and continuing to stir until fully mixed to obtain the solvent matrix.

[0012] In some technical solutions, the mass percentages of the binder, the modifier, the pH adjuster and the film-forming agent in the solvent matrix are 58-77wt.%, 1-3wt.%, 2-4wt.%, and 20-35wt.%, respectively.

[0013] In some technical schemes, the step of dispersing the zinc powder particles in the solvent matrix includes: at room temperature, the zinc powder particles are prepared into a zinc powder suspension, then slowly poured into the solvent matrix, and evenly dispersed by electromagnetic stirring to obtain the anti-corrosion coating.

[0014] In some technical solutions, the step of preparing the zinc powder particles into a zinc powder suspension includes: adding the zinc powder particles into NMP, stirring and dispersing them evenly, to obtain the zinc powder suspension.

[0015] The present invention adopts the above technical solution to have at least the following beneficial effects:

[0016] The anti-corrosion coating provided by the present invention utilizes the electrochemical principle and uses metal zinc as the anode, which is more active than the steel structure, replenishes electrons on the surface of the steel structure and prevents it from being oxidized; and the preparation method is simple.

[0017] (1) The anti-corrosion coating developed by the present invention cleverly uses the principle of electrochemical protection, selects zinc with nano-sized particles as the anode material, and the activity of metallic zinc is higher than that of steel structure, so it can react preferentially in a corrosive environment, effectively replenishing the electrons on the surface of the steel structure, forming a solid protective barrier, thereby effectively preventing the steel structure of the factory from corrosion and increasing its life. In addition, the preparation method of the anti-corrosion coating is simple, easy to operate, and suitable for industrial large-scale production and application;

[0018] (2) The anticorrosive coating provided by the present invention is not only based on the principle of efficient electrochemical protection, but also introduces a variety of functional reagents such as modifiers and pH regulators to comprehensively improve the performance of the anticorrosive coating. The introduction of these reagents enhances the adhesion and durability of the coating, ensuring that the anticorrosive coating can more stably play its protective role in a complex and changeable industrial environment, providing more comprehensive and lasting protection for steel structures. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0020] Coating protection technology is one of the core means to protect the steel structure of large industrial plants from corrosion. High-quality coatings can effectively isolate the steel structure from contact with external corrosive media, greatly extending the service life of the steel structure. The anti-corrosion principle of general anti-corrosion coatings mainly lies in three aspects: chemistry, physics and electrochemistry: the chemical principle neutralizes harmful acid and alkali substances and converts them into neutral and harmless substances to protect the materials in the coating from corrosion; the physical principle is to use the anti-corrosion coating to form a barrier to separate the protective material from external corrosive substances; the electrochemical action is to add specific ingredients to the anti-rust coating, such as chromate. When water and oxygen penetrate the coating, these ingredients will react to form anti-corrosion ions, thereby passivating the metal surface, preventing the dissolution of metal ions, and achieving an anti-corrosion effect.

[0021] Electrochemical protection technology plays an important role in the anti-corrosion technology of steel structures in large industrial plants. In particular, cathodic protection technology effectively slows down or stops the corrosion process by turning the steel structure into a cathode. The principle of this technology is to use external current or sacrificial anode method to replenish electrons on the surface of the steel structure to prevent it from oxidation.

[0022] The present invention is based on the above-mentioned electrochemical protection principle and uses metal zinc, which is more active than the steel structure, as the anode. In this configuration, the anode metal zinc will be dissolved first, thereby effectively protecting the steel structure from corrosion. The following is a specific technical implementation scheme of the present invention:

[0023] Example 1

[0024] The present embodiment provides an anti-corrosion coating, comprising: zinc powder particles and a solvent matrix, wherein the particle size of the zinc powder particles is nanometer-sized, and the particle size of the zinc powder particles is preferably 50nm-90nm, and the mass percentage of the zinc powder particles in the anti-corrosion coating is 1-15wt.%.

[0025] Nano-sized zinc powder particles can be prepared by a direct current arc plasma method. After the zinc powder is obtained, it is quickly dispersed in a high-viscosity polar organic solvent to form a 5-25wt.% suspension.

[0026] In some embodiments, the above-mentioned solvent matrix includes a binder, a modifier, a pH adjuster and a film-forming agent, and the mass percentages of the binder, the modifier, the pH adjuster and the film-forming agent in the anti-corrosion coating are 30-58wt.%, 0.5-1.2wt.%, 1-3wt.% and 20-35wt.%, respectively.

[0027] That is, the components of the anticorrosive coating and the mass percentage of each component are: 1-15wt.% zinc powder particles, 30-58wt.% binder, 0.5-1.2wt.% modifier, 1-3wt.% pH regulator and 20-35wt.% film-forming agent.

[0028] Preferably, the binder is sodium water glass, the modifier is water glass modifier, the pH adjuster is ammonium acetate, and the film-forming agent is water-based hydroxypropyl resin.

[0029] More preferably, the water glass modifier is any one of sodium lauryl sulfate, sodium carboxymethyl cellulose, and dipotassium hydrogen phosphate.

[0030] Example 2

[0031] Based on Example 1, this example provides a method for preparing the anti-corrosion coating: the anti-corrosion coating can be obtained by dispersing zinc powder particles in a solvent matrix.

[0032] In some embodiments, the step of dispersing the zinc powder particles in the solvent matrix specifically includes:

[0033] At room temperature, zinc powder particles are prepared into a zinc powder suspension, which is then slowly poured into a solvent matrix and evenly dispersed by electromagnetic stirring to obtain an anti-corrosion coating, which can be stored at room temperature (18°C-40°C).

[0034] Preferably, the stirring and dispersing time of the zinc powder suspension and the solvent matrix is ​​0.5-1 h.

[0035] In some embodiments, the step of preparing the zinc powder particles into a zinc powder suspension comprises:

[0036] Zinc powder particles are added to NMP (N-methylpyrrolidone) and dispersed uniformly by electromagnetic stirring to obtain a zinc powder suspension, that is, the preparation method using the DC arc plasma method described in Example 1. After the zinc powder is obtained, it is quickly dispersed in a high-viscosity polar organic solvent to form a 5-25wt.% suspension.

[0037] In some embodiments, the preparation steps of the above-mentioned solvent matrix are: weigh the binder, modifier, pH adjuster and film-forming agent according to the ratio, first dilute the binder, then add the modifier and pH adjuster in sequence and stir, add the obtained mixture dropwise into the film-forming agent, continue stirring until fully mixed, and obtain the solvent matrix.

[0038] Furthermore, the mass percentages of the above-mentioned binder, modifier, pH adjuster and film-forming agent in the solvent matrix are 58-77wt.%, 1-3wt.%, 2-4wt.%, and 20-35wt.%, respectively.

[0039] Preferably, the binder, modifier, pH adjuster and film former are sodium water glass, water glass modifier, ammonium acetate and water-based hydroxypropyl resin, respectively.

[0040] Furthermore, when the binder is sodium water glass, the dilution step is: pour 30 mL of deionized water into the sodium water glass for dilution.

[0041] Furthermore, the above-mentioned binder, modifier and pH adjuster are stirred for 30 to 40 minutes.

[0042] Based on Example 1 and Example 2, the anti-corrosion coating and the preparation method thereof provided by the present invention are described below in conjunction with specific examples.

[0043] Example 3

[0044] The components in the anti-corrosion coating in this embodiment and the mass percentage of each component are: 1wt.% zinc powder particles, 30wt.% binder, 0.5wt.% modifier, 1wt.% pH adjuster and 20wt.% film-forming agent.

[0045] The preparation method is as follows:

[0046] (1) preparing a zinc powder suspension: weighing zinc powder particles of nanometer size according to the above ratio, adding them into NMP (N-methylpyrrolidone) respectively, and dispersing them evenly by electromagnetic stirring to obtain a zinc powder suspension;

[0047] (2) Preparation of solvent matrix: Pour 30 mL of deionized water into sodium water glass for dilution, then add water glass modifier and ammonium acetate in sequence, stir thoroughly for 30 to 40 minutes, then slowly drop the mixture into the aqueous hydroxypropyl resin and stir thoroughly to obtain the solvent matrix.

[0048] The components of the above solvent matrix and the mass percentage of each component in the solvent matrix are: 58wt.% of sodium water glass, 1wt.% of water glass modifier, 2wt.% of ammonium acetate, and 20wt.% of water-based hydroxypropyl resin.

[0049] (3) At room temperature, slowly pour the zinc powder suspension into the solvent matrix and disperse it by electromagnetic stirring for 0.5 h to obtain the anti-corrosion coating, which is then stored at room temperature (18°C-40°C).

[0050] Example 4

[0051] The components of the anti-corrosion coating in this embodiment and the mass percentage of each component are: 8wt.% zinc powder particles, 44wt.% sodium water glass, 0.85wt.% water glass modifier, 2wt.% ammonium acetate and 27.5wt.% water-based hydroxypropyl resin.

[0052] The preparation method is as follows:

[0053] (1) preparing a zinc powder suspension: weighing zinc powder particles of nanometer size according to the above ratio, adding them into NMP (N-methylpyrrolidone) respectively, and dispersing them evenly by electromagnetic stirring to obtain a zinc powder suspension;

[0054] (2) Preparation of solvent matrix: Pour 30 mL of deionized water into sodium water glass for dilution, then add water glass modifier and ammonium acetate in sequence, stir thoroughly for 30 to 40 minutes, then slowly drop the mixture into the aqueous hydroxypropyl resin and stir thoroughly to obtain the solvent matrix.

[0055] The components of the above solvent matrix and the mass percentage of each component in the solvent matrix are: 58wt.% of sodium water glass, 1wt.% of water glass modifier, 2wt.% of ammonium acetate, and 20wt.% of water-based hydroxypropyl resin.

[0056] (3) At room temperature, slowly pour the zinc powder suspension into the solvent matrix and disperse it by electromagnetic stirring for 0.5 h to obtain the anti-corrosion coating, which is then stored at room temperature (18°C-40°C).

[0057] Example 5

[0058] The components of the anti-corrosion coating in this embodiment and the mass percentage of each component are: 15wt.% zinc powder particles, 58wt.% sodium water glass, 1.2wt.% water glass modifier, 3wt.% ammonium acetate and 35wt.% water-based hydroxypropyl resin.

[0059] The preparation method is as follows:

[0060] (1) preparing a zinc powder suspension: weighing zinc powder particles of nanometer size according to the above ratio, adding them into NMP (N-methylpyrrolidone) respectively, and dispersing them evenly by electromagnetic stirring to obtain a zinc powder suspension;

[0061] (2) Preparation of solvent matrix: Pour 30 mL of deionized water into sodium water glass for dilution, then add water glass modifier and ammonium acetate in sequence, stir thoroughly for 30 to 40 minutes, then slowly drop the mixture into the aqueous hydroxypropyl resin and stir thoroughly to obtain the solvent matrix.

[0062] The components of the above solvent matrix and the mass percentage of each component in the solvent matrix are: 58wt.% of sodium water glass, 1wt.% of water glass modifier, 2wt.% of ammonium acetate, and 20wt.% of water-based hydroxypropyl resin.

[0063] (3) At room temperature, slowly pour the zinc powder suspension into the solvent matrix and disperse it by electromagnetic stirring for 0.5 h to obtain the anti-corrosion coating, which is then stored at room temperature (18°C-40°C).

[0064] Example 6

[0065] The components of the anti-corrosion coating in this embodiment and the mass percentage of each component are: 10wt.% zinc powder particles, 52wt.% sodium water glass, 1wt.% water glass modifier, 2wt.% ammonium acetate and 35wt.% water-based hydroxypropyl resin.

[0066] The preparation method is as follows:

[0067] (1) preparing a zinc powder suspension: weighing zinc powder particles of nanometer size according to the above ratio, adding them into NMP (N-methylpyrrolidone) respectively, and dispersing them evenly by electromagnetic stirring to obtain a zinc powder suspension;

[0068] (2) Preparation of solvent matrix: Pour 30 mL of deionized water into sodium water glass for dilution, then add water glass modifier and ammonium acetate in sequence, stir thoroughly for 30 to 40 minutes, then slowly drop the mixture into the aqueous hydroxypropyl resin and stir thoroughly to obtain the solvent matrix.

[0069] The components of the above solvent matrix and the mass percentage of each component in the solvent matrix are: 58wt.% of sodium water glass, 1wt.% of water glass modifier, 2wt.% of ammonium acetate, and 20wt.% of water-based hydroxypropyl resin.

[0070] (3) At room temperature, slowly pour the zinc powder suspension into the solvent matrix and disperse it by electromagnetic stirring for 0.5 h to obtain the anti-corrosion coating, which is then stored at room temperature (18°C-40°C).

[0071] On the basis of the above embodiments, the present invention also provides a comparative test of the above anti-corrosion coating and conventional coating in terms of acid salt spray resistance and alkaline salt spray resistance:

[0072] The test set up three groups of sample coatings, a total of 12 groups of specimens, see Table 1 for details.

[0073] Among them, sample 1 is: 140 μm of the anticorrosive coating with the composition shown in Example 5. Sample 2 is: 120 μm epoxy zinc-rich (60%) primer + 120 μm epoxy micaceous iron intermediate paint + 80 μm polyurethane topcoat. Sample 3 is: 70 μm inorganic silicate zinc-rich primer + 70 μm epoxy iron red sealer + 70 μm epoxy micaceous iron intermediate paint + 80 μm polyurethane topcoat.

[0074]

[0075] The Q235 steel plate specimens with a prefabricated size of 100mm×80mm×8mm were derusted, with a surface treatment grade of Sa2.5 and a surface roughness of 40-70μm. The components were polished smooth with 800-mesh sandpaper to remove oil stains and metal powder from the surface. The coating was evenly applied to the surface of the specimen, requiring no gaps or leaks. After the coating was completed, it was air-dried and then placed at room temperature for curing. The prepared specimens were placed in a salt spray chamber, and the temperature in the chamber was controlled at (40±2)℃. The pH value of the acid salt spray test was 2-2.5, the pH value of the alkaline salt spray test was 11-11.5, and the spray volume was 3-4mL / h.

[0076] (I) Acid resistance test results:

[0077] ① After 1060h, there was no change in the sample plates. No obvious phenomenon was found in the scratch of sample 1, but the scratch of sample 2 caused blistering of 3mm and brown rust, and the scratch of sample 3 caused rust and blistering of 1mm.

[0078] ② After 1360h, rust and blistering appeared on sample 1 after scratching, and the rust and blistering was 2mm. The rust and blistering of sample 2 and sample 3 expanded to 5mm and 3mm respectively.

[0079] ③1750h, sample 1 had 3mm of rust and blistering at the scratched part, sample 2 had level 3 powdering on the flat plate, sample 2 had 7mm of rust and blistering at the scratched part, and sample 3 had 4mm of rust and blistering at the scratched part.

[0080] ④ After 2050h, the rust on the scratched part of sample 2 was 13mm, and the blistering was level 5. The rust and blistering on the scratched part of sample 1 and sample 3 increased to 5 and 6mm respectively.

[0081] ⑤There is no obvious phenomenon in all samples after 2250h compared with the previous ones.

[0082] ⑥After 3000h, the rust and blistering at the scratched part of sample 1 was 9mm, the rust and blistering at the scratched part of sample 2 was 17mm, and the blistering was level 6. The flat plate of sample 3 was powdered at level 3, the rust and blistering at the scratched part was 8mm, and the blistering was level 5.

[0083] (II) Alkali resistance test results:

[0084] ① After 1060h, no changes were observed on all sample plates. Sample 1 had 3 places where bubbles started to form at the scratches. Sample 2 had yellow rust bubbles of 5mm at the scratches. Sample 3 had no obvious signs of rust.

[0085] ②1360h, all sample plates showed no changes. The number of rust spots on sample 1 did not change significantly compared with before, but the area increased slightly. The scratched rust and peeling area of ​​sample 2 expanded, the color of the rusted position turned brown, and the blister was 12mm. There was no rust at the scratched position of sample 3.

[0086] ③ After 1750h, there was no change in the plates of Samples 1 and 2, but Grade 4 powdering occurred in the plate of Test 3. The surface of the steel plate was covered with white flocculent oxide scale but no rust occurred. The number of rust blister points at the scratched area of ​​Sample 1 increased to 5, and the number of rust blister points at the scratched area of ​​Sample 2 increased to 19mm. Grade 4 powdering occurred in the scratched area of ​​Sample 3.

[0087] ④ At 2050h, the rust on the scratched area of ​​sample 2 continued to increase to 24mm, and the brown bubbles gradually turned into black bubbles. The other samples showed no obvious changes compared with 1750h.

[0088] ⑤ After 2250h of testing, sample 1 had 6 rust and blistering spots at the scratches, sample 2 had rust and blistering of 28mm at the scratches, and sample 3 had grayish white blistering on both the flat plate and the scratches.

[0089] ⑥ At 2750h, sample 1 had 7 rust and blisters at the scratched areas, and sample 3 had an increasing number of blisters, with brown rust appearing at the scratched areas.

[0090] ⑦ After 3000h, black rust appeared in the area where sample 1 was scratched and blistered, sample 2 was scratched and corroded over a large area, and the rust on sample 3 continued to expand.

[0091] Under the acid salt spray resistance test conditions, rust first appeared at the scratched areas of samples 2 and 3, followed by sample 1. The flat specimen of sample 3 showed powdering, and the scratched specimen showed powdering and rust blistering.

[0092] Under the alkaline salt spray test conditions, no obvious phenomenon occurred on the flat plates of sample 1 and sample 2, but powdering and blistering occurred on the flat plate of sample 3. When sample 1 was scratched, only part of the blistering position was rusted, while when sample 2 was scratched, a large area of ​​corrosion occurred. When sample 3 was scratched, powdering, blistering, rusting and other phenomena occurred, and the rust was obvious.

[0093] In summary, it can be seen that the acid and alkali resistance of the anti-corrosion coating of sample 1 of the present invention is stronger than that of the traditional anti-corrosion coating represented by samples 2 and 3.

[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. An anti-corrosion coating, characterized in that: include: Zinc powder particles and solvent matrix, The particle size of the zinc powder particles is nanometer size. The mass percentage of the zinc powder particles in the anti-corrosion coating is 1 to 15 wt.%.

2. The anticorrosive coating according to claim 1, characterized in that: The solvent matrix includes a binder, a modifier, a pH adjuster and a film former, The mass percentages of the binder, the modifier, the pH adjuster and the film-forming agent in the anti-corrosion coating are 30-58wt.%, 0.5-1.2wt.%, 1-3wt.% and 20-35wt.%, respectively.

3. The anticorrosive coating according to claim 2, characterized in that: The binder is sodium water glass; The modifier is a water glass modifier; The pH regulator is ammonium acetate; The film-forming agent is water-based hydroxypropyl resin.

4. The anticorrosive coating according to claim 3, characterized in that: The water glass modifier is any one of sodium lauryl sulfate, sodium carboxymethyl cellulose and dipotassium hydrogen phosphate.

5. The anticorrosive coating according to claim 1, characterized in that: The particle size of the zinc powder particles is 50nm-90nm.

6. The method for preparing the anticorrosive coating according to any one of claims 1 to 5, characterized in that: The zinc powder particles are dispersed in the solvent matrix to obtain the anti-corrosion coating.

7. The preparation method according to claim 6, characterized in that: Also includes: Prepare the solvent matrix: weigh the binder, modifier, pH adjuster and film former according to the ratio, dilute the binder first, then add the modifier and pH adjuster in sequence and stir, add the obtained mixture dropwise into the film former, continue stirring until fully mixed, and obtain the solvent matrix.

8. The preparation method according to claim 7, characterized in that: Also includes: The mass percentages of the binder, the modifier, the pH adjuster and the film-forming agent in the solvent matrix are 58-77wt.%, 1-3wt.%, 2-4wt.%, and 20-35wt.%, respectively.

9. The preparation method according to claim 6, 7 or 8, characterized in that: The step of dispersing the zinc powder particles in the solvent matrix comprises: At room temperature, the zinc powder particles are prepared into a zinc powder suspension, which is then slowly poured into the solvent matrix and evenly dispersed by electromagnetic stirring to obtain the anti-corrosion coating.

10. The preparation method according to claim 9, characterized in that: Also includes: The step of preparing the zinc powder particles into a zinc powder suspension comprises: The zinc powder particles are added into NMP, and stirred to disperse them uniformly to obtain the zinc powder suspension.